ROUTLEDGE HANDBOOK OF SPORT SECURITY (ROUTLEDGE, 2026)
This book provides an in-depth analysis of security issues and concerns in contemporary sport. Featuring the work of leading researchers and practitioners from around the world, it offers practical, evidence-based commentary and guidance.Drawing on the latest research evidence, the book examines the multiple stakeholders, agencies, and organizations involved in providing a safe space for spectators, participants, staff, organizations, communities, and sponsors. It considers the coordination of private and public entities in the sports security ecosystem, including facility management, event management, law enforcement, emergency management, emergency medical services, and state/federal government partners, as well as the private sector organizations providing support services. The book also offers a comprehensive analysis of key issues and debates in contemporary sport security, including terrorism, cybersecurity, spectator violence, planning and assessment guidance for sport venues and events of all sizes, management and policy considerations for leaders and decision-makers, and the lessons learned from critical incidents. It introduces the core principles of research methods in sport security and looks ahead at future developments in this rapidly changing field.This is essential reading for any advanced student, researcher, practitioner, or policy-maker with an interest in sport studies, security studies, event studies, criminal justice, management, or public policy.
Keywords: Sports -- Safety measures.; Sports facilities -- Security measures.; Sports facilities -- Safety measures.; Special events -- Security measures.; Special events -- Safety measures.; elektronické knihy; electronic books